Oral Vitamin D Supplements Increase Serum 25-Hydroxyvitamin D in Postmenopausal Women and Reduce Bone Calcium Flux Measured by 41Ca Skeletal Labeling. Issue 10 (2nd September 2015) - Schild, Andreas; Herter-Aeberli, Isabelle; Fattinger, Karin; Anderegg, Sarah; Schulze-König, Tim; Vockenhuber, Christof; Synal, Hans-Arno; Bischoff-Ferrari, Heike; Weber, Peter; von Eckardstein, Arnold; Zimmermann, Michael B
Abstract: Background: Ensuring adequate vitamin D status in older adults may reduce the risk of osteoporosis. The serum 25-hydroxyvitamin D [25(OH)D] concentration is the recommended biomarker of vitamin D status, but the optimal serum 25(OH)D concentration for bone health in postmenopausal women remains unclear. Objective: The aim of this study was to apply the highly sensitive 41 Ca skeletal labeling technique and the measurement of urinary 41 Ca: 40 Ca ratios to determine the serum 25(OH)D concentration that has greatest benefit on bone calcium flux in postmenopausal women. Methods: We administered a mean intravenous 41 Ca dose of 870 pmol to healthy postmenopausal women [ n = 24, age (mean ± SD): 64 ± 6.0 y] without osteoporosis. After 6 mo, at the nadir of their wintertime serum 25(OH)D status, each of the women sequentially consumed daily oral cholecalciferol supplements of 10, 25, and 50 μg/d (in this order), each for 3 mo. We assessed serum 25(OH)D concentrations monthly and urinary 41 Ca: 40 Ca ratios biweekly. 41 Ca: 40 Ca ratios were measured with low-energy accelerator mass spectrometry. With the use of pharmacokinetic analysis, we determined the effect of varying serum 25(OH)D concentrations on 41 Ca transfer rates. Results: At baseline, the mean (95% CI) serum 25(OH)D concentration was 16.2 (13.5, 18.8) μg/L. After the first, second, and third intervention periods, mean (95% CI) serum 25(OH)D increased to 29.8 (27.2, 32.4), 36.9 (34.2, 39.7), and 46.6 (41.2, 52.0) μg/L, respectively. Supplementation was associated with a downward shift in the urinary 41 Ca: 40 Ca ratio compared with the predicted 41 Ca: 40 Ca ratio without vitamin D supplementation. In the model, the most likely site of action of the increase in serum 25(OH)D was transfer from the central compartment to a fast exchanging compartment. At this transfer rate, predicted values were a concentration with half-maximal effect of 2.33 μg/L and an estimate of the maximal effect of 31.7%. After the first, second, and third intervention periods, the mean changes in this transfer rate were +18.0%, +25.7%, and +28.5%, respectively. Conclusion: In healthy postmenopausal women, increasing serum 25(OH)D primarily affects calcium transfer from the central compartment to a fast exchanging compartment; it is possible that this represents transfer from the extracellular space to the surface of bone. A serum 25(OH)D concentration of ∼40 μg/L achieves ∼90% of the expected maximal effect on this transfer rate. This trial was registered at clinicaltrials.gov as NCT01053481.